2015
DOI: 10.2298/apt1546001b
|View full text |Cite
|
Sign up to set email alerts
|

Techno-functional properties of pea (Pisum sativum) protein isolates: A review

Abstract: Due to high nutritive quality, good techno-functional properties and low cost, legume protein products are becoming the most appropriate alternative to protein products of animal origin. In food industries, these products are usually used as techno-functional additives which provide specific characteristics of final food products. Legume proteins are commonly used as flour, concentrates, and isolates. The greatest application on industrial scale has soy proteins, and to a lesser extent, in the past 20 years, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 67 publications
6
78
0
3
Order By: Relevance
“…As shown in Figure 2, ES increased rapidly as pH moved away from the isoelectric point of the meat proteins. Moreover, the main pea proteins have very low emulsion stability in the pI (isoelectric point) range (Barać et al, 2015). Varying pH, ionic species, and ionic strength cause pea proteins to form different network structures (Munialo et al, 2014).…”
Section: Figure 2 Effects Of Ph and Pea On The Emulsion Stability Of mentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Figure 2, ES increased rapidly as pH moved away from the isoelectric point of the meat proteins. Moreover, the main pea proteins have very low emulsion stability in the pI (isoelectric point) range (Barać et al, 2015). Varying pH, ionic species, and ionic strength cause pea proteins to form different network structures (Munialo et al, 2014).…”
Section: Figure 2 Effects Of Ph and Pea On The Emulsion Stability Of mentioning
confidence: 99%
“…There is a significant relationship between EA and pH values (Neto et al, 2001) affecting the solubility of protein and polysaccharide and leading to differences in net electrical charge. Barać et al (2015) suggested that the emulsification activity is a minimum in the isoelectric point range of major pea proteins. Moreover, they reported that as the pH is moved away from pI, the emulsifying properties improve due to intensive dissociation, which is more evident in the case of legumin (Neto et al, 2001).…”
Section: Figure 2 Effects Of Ph and Pea On The Emulsion Stability Of mentioning
confidence: 99%
See 2 more Smart Citations
“…Robles-Ramírez, et al [18] evaluated the effect of germinated soy protein on the growth of HeLa cervical cancer cells in female athymic mice. They observed that teins [40]. A diet high in dry pea has been demonstrated to be effective in lowering the incidence of colon cancer, type-2 diabetes, LDL-cholesterol and heart disease [36].…”
Section: Soybeansmentioning
confidence: 99%